Syntactic position and functions of an adjective in the sentence structure in Persian compared to Russian - Yarzada, Bibi Saliha (Филология: научные исследования, 2024)
This article is devoted to the study of the syntactic position of the adjective in the structure of the Persian sentence in comparison with the Russian language. The article pays special attention to the functional aspect, which is implemented by adjectives. The syntactic roles of semantic units are also considered. In this article, the features of adjectives in the Persian language are analyzed on the basis of structural and syntactic criteria adopted in comparative grammar. By comparing the functions and features of adjectives, we can talk about the similarities and differences in Persian and Russian, the importance of adjectives for the formulation of thought and the place of adjectives in literary and journalistic texts. Attention is also paid to the dependence of the adjective on the noun and the placement in the preposition and postposition and the change of meaning in the context of these sentences. This article is based on a comparative analysis, when the evaluation of Persian adjectives is realized in comparison with Russian adjectives both in the field of functions and in the field of unit typology. The novelty of the research is manifested in the comparative aspect of the Russian and Persian adjectives. Morphologically, the most important difference between adjectives in Persian and Russian is the presence of grammatical gender in the Russian language and its absence in the Persian language. During the analysis, it was concluded that, although there is a great difference in the syntactic functionality of the Persian and Russian adjectives, we can say that the main function is to expand the meaning of the noun and clarify it, nevertheless it is respected. At the same time, an adjective in Farsi plays the role of other elements, in particular, a numeral, an adverb, or even a predicate.